Opportunities and Challenges of Utilizing Blockchain Technology in Marketing Management: A Case Study on the Financial Industry: A UTAUT Theory Approach - Ratna Dewi; Suriyanti Mangkona (International Journal of Artificial Intelligence Research, 2022)
This research discusses the utilization of blockchain technology in financial industry marketing and the implementation of digital marketing management theory. Blockchain technology offers the potential to improve efficiency and security in the financial industry marketing process. In the context of customer identity verification, blockchain can be used as a secure and encrypted repository of identity data. This speeds up the verification process, reduces operational costs, and minimizes the risk of data leakage. Case studies in the banking, insurance, and digital marketing industries demonstrate the significant benefits of blockchain implementation in customer identity verification. However, technical, infrastructure, and regulatory challenges must be overcome to maximize the potential of this technology. In the context of blockchain marketing theory, this technology provides a level of transparency, active customer participation, efficient data management, smart contract execution, and innovation of new products and services. Companies in the financial industry need to consider the challenges that may arise, such as complex regulations, slow technology adoption, and security concerns.